1999
DOI: 10.1093/hmg/8.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the circulating concentration of transforming growth factor type beta1

Abstract: The concentration of transforming growth factor beta (TGF-beta) in plasma has been correlated with the development of several diseases, including atherosclerosis and certain forms of cancer. However, the mechanisms that control the concentration of TGF-beta in plasma are poorly understood. In a study of 170 pairs of female twins (average age 57.7 years) we show that the concentration of active plus acid-activatable latent TGF-beta1 [(a+l) TGF-beta therefore is predominantly under genetic control (heritability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
539
3
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 679 publications
(581 citation statements)
references
References 26 publications
24
539
3
5
Order By: Relevance
“…Grainger reported that individuals homozygous for -509T/T had higher plasma concentrations of TGF-β1 than heterozygous C/T or homozygous C/C individuals (Grainger et al, 1999). The genotype distribution and allele frequencies among the healthy controls in our study were parallel to the literature.…”
Section: Discussionsupporting
confidence: 81%
“…Grainger reported that individuals homozygous for -509T/T had higher plasma concentrations of TGF-β1 than heterozygous C/T or homozygous C/C individuals (Grainger et al, 1999). The genotype distribution and allele frequencies among the healthy controls in our study were parallel to the literature.…”
Section: Discussionsupporting
confidence: 81%
“…Twin studies are a useful tool to assess the heritability of cytokine production. 21 Our results confirm a considerable genetic component for IL-10 production upon LPS stimulation with a heritability of 0.5. This means that 50% of IL-10 production are determined by genetic factors whereas the other half is accounted for by additive environmental influences.…”
Section: Discussionsupporting
confidence: 77%
“…The two SNPs have been reported to act by altering the rate of secretion of TGFB1 and hence the circulating levels of mature protein [33][34][35][36]. However, not all studies have demonstrated such a relationship [37] -the presence, in the circulation, of both latent and activated forms may complicate the interpretation of studies on circulating levels.…”
Section: Discussionmentioning
confidence: 99%